The potential of adapting rural cultural landscape characteristics in Malaysian urban residential area - Ismail, Nor Atiah; Egoz, Shelley; Cushman, Grant (Universiti Putra Malaysia Press, 2011)
Substantial rural-urban migration in Malaysia between 1971 and 1975 is underpinned by aspirations for better economic, educational and social opportunities. The shift to an urban area requires adaptation to a totally different environment. Migrants continue to practice their local culture and kampong (village) values even atter they have relocated to new housing estates. The responsive rural cultural landscape characteristics embody the residents' way of life tram the traditional village and are posited to have great potential for adaptation in urban residential area in Malaysia. This article would like to encourage landscape architects to incorporate residential cultural identities in contemporary housing development that would inspire their residents' aspirations and identity of 1Malaysia.